THE EFFECTIVENESS OF USING MIND MAPPING TECHNIQUE TOWARD THE STUDENTS’ ACHIEVEMENT IN WRITING DESCRIPTIVE TEXT - Dianto, Roni; Basuni, Muh. (Pusat Pengembangan Bahasa IAIN Tulungagung, 2015)
In learning descriptive text, the students may be confused what they want to write because they didn’t have idea even though the teacher has been given the object. Therefore, in this study, the researcher will try to apply mind mapping technique. This technique is expected to solve the difficulty of students in writing descriptive text. The result of the research showed that the students’ mean before treatment was 51, 10. And the students’ mean after the treatment was 67, 10. The significant level two tails is 0, 00 and the standard level of significant is 0, 05. By comparing the significant level and the standard level significant, the researcher got calculation. It is known that the significant level two tails is < the standard level significant (0, 00< 0, 005). Because the significant level two tails is < the standard level significant, it can be concluded that the alternative hypothesis (Ha) is accepted and the null hypothesis is rejected. It means that there is significant different score in writing descriptive text before being taught using mind mapping technique and after taught using mind mapping technique. The conclusion is mind mapping technique is improving students’ achievement in writing descriptive text. Finally, it can be concluded that mind mapping can be applied of teacher during teaching and learning process.